القيم المرغوبة في الكتب المنهجية في القرن الحادي و العشرين من وجهة نظر التربويين و النفسيين - عزيز, عمر ابراهيم (Sulaimani Journal for Humanities, 2002)
1- Acontent Analysis of Reading Textbook in Terms of Moral_Ambererombic ,Chrlotte Maning Value. MX Columbia University, 1974. 2- Banks, James A. "Content Analysis of the Black American In Textbook, 71 Banks, James A, Teaching Social Studies to Culturally Different Children. Newyork Addison-Wesley, 1977. 3- Chaplin, J. P. Dictionary of Psychology. Newyork, Dell, 1971. 4- Good. Carter V (ed) Dictionary of Education 3rd ed .Newyork, Mcgrawhill, 1973. 5- Stogdill, Ralph. Meilvin. Individual Behavior and Group Achievement. Newyork. Oxford University, 1959. 6- White, Ralph K. Value-Analysis: The Nature and use of the Method. Newyork Jersey, Libration Press, 1951.